Crop parameters and spectral response of coffee (Coffea arabica L.) areas within the State of Minas Gerais, Brazil - Vieira, Tatiana Grossi Chquiloff; Alves, Helena Maria Ramos; Lacerda, Marilusa Pinto Coelho; Veiga, Ruben Delly; Epiphanio, José Carlos Neves (Coffee Science - ISSN 1984-3909, 2007)
This work compares coffee plantation (Coffea arabica L.) characteristics to their spectral responses in TM/ Landsat images to obtain identification patterns to be used in mapping and monitoring of coffee crops in the state of Minas Gerais using remote sensing. The fieldwork involved selection of representative areas from the main coffee production regions of the state, with definition of study areas from where the coffee parameters and environmental data were collected. Two pilot-areas representative of the physiographic regions, Alto Paranaíba and Sul de Minas were selected for the study. The field data and TM/Landsat images were treated with the SPRING geographic information system. The reflectance data, as well as the remaining data collected in the field, were organized in a statistical programme for correlation studies. The statistical analysis showed that, among the fourteen variables evaluated, the highest correlation was observed between reflectance measured in the near infrared zone and the percentage of area covered by the plant canopies. This parameter reflects the effects of other crop variables, such as size, diameter, density, vegetative vigour and productivity. Results show that, due to the great variability of the crop and the limitations imposed by TM/Landsat products, the definition of a pattern is unlikely. Nevertheless, for productive adult coffee plants in good vegetative state, the survey and monitoring of the crop can be carried out using TM/Landsat images, particularly in regions like Alto Paranaíba , where the landscape is mostly of gently undulating slopes and the coffee fields are more extensive and homogeneous.